PROFIL OSTEOBLAS DAN OSTEOKLAS TULANG ALVEOLAR PADA MODEL TIKUS DIABETES TAHAP AWAL DENGAN APLIKASIGAYA ORTODONTI YANG BERBEDA - Hikmah, Nuzulul (El-Hayah : Jurnal Biologi, 2015)
Orthodontic tooth movement is obtained through alveolar bone remodeling. Alveolar bone remodeling includes resorption process that played by osteoclasts and bone formed process that played by osteoblasts. Diabetes affects on orthodontic tooth movement. The magnitude of orthodontic force that applied in the early stages of diabetic conditions, would be a consideration of the alveolar bone remodeling process. The purpose of this study was to determine osteoblast and osteoclast profile in early stage of rat diabetic models with different orthodontic force application. 24 Wistar rats were divided into three groups of controls andthree groups of early stage of diabetic treatment with different orthodontic force application (10, 20, and 30 gramforce/grf). The results showed an increased of osteoclast numbers in early stage of diabetes and will be increased along with the increased of orthodontic force. The results also showed a decreased of osteoblast number in early stage of diabetes, but it would be increased along with the increased of orthodontic force.